The actin filament-binding protein coronin regulates motility in Plasmodium sporozoites - Bane, Kartik; Lepper, Simone; Kehrer, Jessica; Sattler, Julia M.; Singer, Mirko; Reinig, Miriam; Klug, Dennis; Heiß, Kirsten; Baum, Jake; Müller, Ann-Kristin; Frischknecht, Friedrich (PLoS pathogens, 2016)
Parasites causing malaria need to migrate in order to penetrate tissue barriers and enter host cells. Here we show that the actin filament-binding protein coronin regulates gliding motility in Plasmodium berghei sporozoites, the highly motile forms of a rodent malaria-causing parasite transmitted by mosquitoes. Parasites lacking coronin show motility defects that impair colonization of the mosquito salivary glands but not migration in the skin, yet result in decreased transmission efficiency. In non-motile sporozoites low calcium concentrations mediate actin-independent coronin localization to the periphery. Engagement of extracellular ligands triggers an intracellular calcium release followed by the actin-dependent relocalization of coronin to the rear and initiation of motility. Mutational analysis and imaging suggest that coronin organizes actin filaments for productive motility. Using coronin-mCherry as a marker for the presence of actin filaments we found that protein kinase A contributes to actin filament disassembly. We finally speculate that calcium and cAMP-mediated signaling regulate a switch from rapid parasite motility to host cell invasion by differentially influencing actin dynamics.
Gesehen am 19.08.2020